Familial C4B deficiency and immune complex glomerulonephritis - Soto, K (2010)
Homozygous complement C4B deficiency is described in a Southern European young female patient with Membranoproliferative Glomerulonephritis (MPGN) type III characterized by renal biopsies with strong complement C4 and IgG deposits. Low C4 levels were independent of clinical evolution or type of immunosuppression and were found in three other family members without renal disease or infections. HLA typing revealed that the patient has homozygous A*02, Cw*06, B*50 at the class I region, and DRB1*08 and DQB1*03 at the class II region. Genotypic and phenotypic studies demonstrated that the patient has homozygous monomodular RCCX in the HLA class III region, with single long C4A genes coding for C4A3 and complete C4B deficiency. Her father, mother, son and niece have heterozygous C4B deficiency. The patient's deceased brother had a history of Henoch-Schönlein Purpura (HSP), an immune complex-mediated proliferative glomerulonephritis. These findings challenge the putative pathophysiological roles of C4A and C4B and underscore the need to perform functional assays, C4 allotyping and genotyping on patients with persistently low serum levels of a classical pathway complement component and glomerulopathy associated with immune deposits.